Beethoven after Napoleon : political romanticism in the late works - Rumph, Stephen C. (California studies in 19th century music ;, 2004)
In this analysis of Beethoven's late style, Stephen Rumph demonstrates how deeply political events shaped the composer's music, from his early enthusiasm for the French Revolution to his later entrenchment during the Napoleonic era. Beethoven after Napoleon challenges accepted views by illustrating the influence of German Romantic political thought in the formation of the artist's mature style. Beethoven's political views, Rumph argues, were not quite as liberal as many have assumed. While scholars agree that the works of the Napoleonic era such as the Eroica Symphony or Fidelio embody enlightened, revolutionary ideals of progress, freedom, and humanism, Beethoven's later works have attracted less political commentary. Rumph contends that the later works show clear affinities with a native German ideology that exalted history, religion, and the organic totality of state and society. He claims that as the Napoleonic Wars plunged Europe into political and economic turmoil, Beethoven's growing antipathy to the French mirrored the experience of his Romantic contemporaries. Rumph maintains that Beethoven's turn inward is no pessimistic retreat but a positive affirmation of new conservative ideals. --From publisher's description.